Connections between the European Pillar of Social Rights and the Hungarian labour law with special regard to Directive (EU) 2019/1152 - Zaccaria, Márton Leó (Zbornik radova Pravnog fakulteta u Novom Sadu, 2022)
The present paper examines two important and up-to-date topics in labour law. First, the analysis focuses on the general aspects and the significance of the European Pillar of Social Rights (EPSR), which is the most recent legal source – except for a couple of directives and regulations based on the EPSR itself – in the social policy of the European Union. It contains several fundamental labour and social rights and one of its main aims is to promote and to strengthen these rights and values throughout the Membes States. At the same time, the EPSR is already having an impact on national labour and social law systems in the EU because of some new pieces of labour law-focused legislation. One of these new laws is the Directive (EU) 2019/1152 of the European Parliament and of the Council (20 June 2019) on transparent and predictable working conditions in the European Union that contains very important new norms regarding both the possible broad concept of the “employment relationship” and the workers’ fundamental rights. Second, the paper focuses on some relevant questions of the Hungarian labour law as a case study, analysing the possible – and already visible – impact of the EPSR and the aforemtnioned new directive. The paper tries to answer some questions based on the paper’s hypotheses centred on the possible change in the Hungarian regulation and legal interpretation taking into account the EPSR and the already cited directive. The analysis is based on the relevant regulations and laws, and the outcomes of the research focus both on some general remarks regarding the EPSR and the Directive (EU) 2019/1152 joint with the conclusions that can be drawn paying attention specifically to the Hungarian labour law system with special attention to the workers’ fundamental rights.
Keywords: European Pillar of Social Rights, Hungarian Labour Code, labour law, workers’ rights